2017
DOI: 10.1051/itmconf/20171204026
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Lurylamine Modified Heteropoly Acid as an Efficient and Recyclable Catalyst for the Hydrolysis Reaction in Aqueous Solution under Microwave

Abstract: Abstract:A new modified phosphotungstic acid (HPW) catalyst (HPW-catal) was synthesized b y a simple mixing method under ambient atmosphere and evaluated for the hydrolysis of sucrose and ethyl acetate under microwave irradiation. The as-synthesized catalyst was characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy(FTIR), and NH3-TPD, which proved that HPW was sucessfully modified with lurylamine and the catalyst still remains the Keggin structure. Significantly, the HPW-catal showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…phosphotungstic acid catalyst. They used several characterization instruments to characterize the catalyst and found that the modified heteropoly acid was still the Keggin structure (Wu et al, 2017 ). As compared with conventional phosphotungstic acid, the luryamine-modified HPA catalyst showed more stable and higher catalytic activity.…”
Section: Hydrolytic Depolymerization Of Biomass With Hpas-based Catalmentioning
confidence: 99%
“…phosphotungstic acid catalyst. They used several characterization instruments to characterize the catalyst and found that the modified heteropoly acid was still the Keggin structure (Wu et al, 2017 ). As compared with conventional phosphotungstic acid, the luryamine-modified HPA catalyst showed more stable and higher catalytic activity.…”
Section: Hydrolytic Depolymerization Of Biomass With Hpas-based Catalmentioning
confidence: 99%